2015
DOI: 10.1016/j.jval.2015.09.2229
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life, Work Productivity, and Daily Activity Among A Sample of Commercially Insured Patients With Irritable Bowel Syndrome With Constipation or Chronic Constipation In The United States

Abstract: Patients with stoma evaluated their life quality only with 42.33 points from the overall 80. ConClusions: Patients with intestinal diseases are defatigable, and have abdominal problems frequently. In case of ulcerative colitis the burden of disease is higher, life quality is less favourable. Stoma negatively affects life quality. The residence is significantly affected by the disease burden and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study contributes uniquely to the large body of research on the effect of IBS on overall quality of life by elucidating the specific behavioral impact of IBS on daily living. Existing quality of life research suggests that IBS is perceived to be as debilitating as the flu 9 and that reported QoL is lower in IBS when compared to gastroesophageal reflux disease, inflammatory bowel diseases, diabetes, and end-stage renal disease 25,26 . Although reasons for such low QoL in IBS have not been clearly identified, it is apparent that the impact of IBS on a patient’s daily life should not be underestimated 27 .…”
Section: Discussionmentioning
confidence: 99%
“…This study contributes uniquely to the large body of research on the effect of IBS on overall quality of life by elucidating the specific behavioral impact of IBS on daily living. Existing quality of life research suggests that IBS is perceived to be as debilitating as the flu 9 and that reported QoL is lower in IBS when compared to gastroesophageal reflux disease, inflammatory bowel diseases, diabetes, and end-stage renal disease 25,26 . Although reasons for such low QoL in IBS have not been clearly identified, it is apparent that the impact of IBS on a patient’s daily life should not be underestimated 27 .…”
Section: Discussionmentioning
confidence: 99%
“…IBS is increasingly being referred to as a disorder of gut-brain interaction to highlight the role of the gut-brain (i.e., mind-body) axis in symptom generation. IBS is characterized by abdominal pain and altered bowel habits (constipation and/or diarrhea), and it is associated with a significant reduction in quality of life, high health care utilization, and comorbidities with other chronic conditions (2)(3)(4). Treatment options for IBS typically include medical therapy, dietary, and life-style interventions as well as mind-body therapies, and the condition is best managed when approached from a biopsychosocial perspective (5).…”
Section: Introductionmentioning
confidence: 99%
“…Its diagnosis is based on patient‐reported symptoms such as infrequent stools, hard/lumpy stool consistency, straining, and incomplete evacuation 2 . Chronic constipation impacts daily activities and adversely affects quality of life 3,4 . Furthermore, it is responsible for substantial health care costs, ranging from $1912 to $11,991 per patient annually 5,6 …”
Section: Introductionmentioning
confidence: 99%